A prospective, multicentre, open‐label, single‐arm clinical trial for treatment of chronic complex diabetic foot wounds with exposed tendon and/or bone: positive clinical outcomes of viable cryopreserved human placental membrane. Issue 3 (3rd August 2016) - Frykberg, Robert G; Gibbons, Gary W; Walters, Jodi L; Wukich, Dane K; Milstein, Farrell C
Abstract: Complex diabetic foot ulcers (DFUs) with exposed tendon or bone remain a challenge. They are more susceptible to complications such as infection and amputation and require treatments that promote rapid development of granulation tissue and, ultimately, reepithelialisation. The clinical effectiveness of viable cryopreserved human placental membrane (vCHPM) for DFUs has been established in a level 1 trial. However, complex wounds with exposed deeper structures are typically excluded from randomised controlled clinical trials despite being common in clinical practice. We report the results of a prospective, multicentre, open‐label, single‐arm clinical trial to establish clinical outcomes when vCHPM is applied weekly to complex DFUs with exposed deep structures. Patients with type 1 or type 2 diabetes and a complex DFU extending through the dermis with evidence of exposed muscle, tendon, fascia, bone and/or joint capsule were eligible for inclusion. Of the 31 patients enrolled, 27 completed the study. The mean wound area was 14·6 cm 2, and mean duration was 7·5 months. For patients completing the protocol, the primary endpoint, 100% wound granulation by week 16, was met by 96·3% of patients in a mean of 6·8 weeks. Complete wound closure occurred in 59·3% (mean 9·1 weeks). The 4‐week percent area reduction was 54·3%. There were no product‐related adverse events. Four patients (13%) withdrew, two (6·5%) for non‐compliance and two (6·5%) for surgical intervention.